The Functional Role of the 3′ Untranslated Region and Poly(A) Tail of Duck Hepatitis A Virus Type 1 in Viral Replication and Regulation of IRES-Mediated Translation - Chen, Jun-Hao; Zhang, Rui-Hua; Lin, Shao-Li; Li, Peng-Fei; Lan, Jing-Jing; Song, Sha-Sha; Gao, Ji-Ming; Wang, Yu; Xie, Zhi-Jing; Li, Fu-Chang; Jiang, Shi-Jin (Frontiers in Microbiology, 2018)
The duck hepatitis A virus type 1 (DHAV-1) internal ribosome-entry site (IRES) element plays an important role in translation initiation and RNA synthesis. A previous study showed that either the complete or a partial deletion of the DHAV-1 3′ untranslated region (3′ UTR) had no impact on viral protein expression. In this study, the functional role of the 3′ UTR and poly(A) tail of DHAV-1 in viral replication and IRES-mediated translation was investigated. The results showed that the 3′ UTR or poly(A) tail length were important for viral genome replication respectively, with a 10- to 15-nucleotide increase in poly(A) tail length resulting in a 12-fold increment in viral copy number. We investigated that 3′ UTR plus poly(A) tail significantly enhance IRES-mediated translation efficiency. Furthermore, 3′ UTR or poly(A) tail could act as an individual element to stimulate DHAV-1 IRES-mediated translation efficiency, and the stimulation values of the 3′ UTR were greater than those of the poly(A)25 tail. More importantly, both 3′ UTR and poly(A) tail are important for maintaining viral genome RNA stability.